Optimization of Bored Pile Foundation Usage in Apartment Development Projects in Batam - Defitri, Hilga; Andriani, Andriani; Hakim, Abdul; Hape, Shafira Rahmadilla (Jurnal Teknik Sipil, 2025)
Batam is actively developing apartments and hotels to support the growing tourism sector. Proper planning of structures and foundations is essential in the construction process to ensure the building's strength. Several factors must be considered when designing bored pile foundations, such as depth, diameter, and pile cap dimensions. Costs increase as the piles' diameter and the pile cap's dimensions expand. Therefore, optimizing the foundation design to achieve the optimal pile diameter, number of piles, and bearing capacity is important while maintaining cost efficiency without compromising foundation safety standards. This study aims to optimize the allowable bearing capacity of the actual bored pile foundation using the N-SPT value approach and compare the costs of executing the actual bored pile foundation with the optimized bored pile foundation. The analysis results show that the actual foundation bearing capacity in the field is 21.038,448 kN, while the optimized foundation has a bearing capacity of 10.812 kN. The cost for the actual bored pile foundation in the field is IDR 604.862.538, while the cost for the optimized pile foundation is IDR 416.517.335. The difference in cost between the two is IDR 188.345.203, indicating a cost saving of 68,86% with the optimized foundation.